Evaluasi dan Proyeksi Kebutuhan Terminal Building Bandar Udara (Studi Kasus Minangkabau International Airport) - Suandi, Oki; Sandhyavitri, Ari; Djuniati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The development of air transportation in Minangkabau International Airport-Padang Pariaman had indicated that the existing capacity of terminal building was overcapacity with average 2,9 million number of passengers per year was no longer able to accommodate the volume of passengers. It also can be identified through the escalation amount of passenger that reach 3,1 million passengers in 2015. The expansion plan was done by forming equation of multiple linier regression between the volume of passenger as dependent variable with total population, PDRB (Product Domestic Regional Bruto), income per capita and tourist as independent variable. The prediction number in certain year was generated with 328377+0.062Pkt equation and tourist variable with -36623+0,097Wtb equation. The result of terminal building expansion plan area in 2035 should not be less than 65.233m2 with 7.402.896 number of passengers capacity and also able to accommodate 3782 passengers during a peak hour.Keywords : Terminal Building, Forecast